ANALISIS CUSTOMER VALUE INDEX DALAM MEMILIH PAKAIAN WANITA DI INDONESIA - Elika Permata; Osa Omar Sharif (SOSIOHUMANITAS, 2020)
The purpose of this paper is to determine the combination attributes of women’s clothing that produced the higest customer value indeks and to know the attributees that are the value driver of women/s clothing. This research is quantitative reaseach with using conjoint analysis method, sampling using nonprobability purposive sampling. This Study is based on primary data collected through a survey from 397 women clothing consumer in Indonesia. After that, conjoint analysis was used to estimate the relative importance of women clothing attributes that ware identified in the women consumer and tread-offs made within this attribute set (combination attributes card). Finding participants identified brand, style, retail store, and price that they used to evaluate women clothing. The paper identified attributes of women clothing that are values by women clothing consumers in Indonesia. In this conjoint analysis respondents identified price as having the bigesht relative importance because have a highet consumer value index, followed by retail store, brand, and style. Women clothing are more likely to be purchased by consumer if they are reasonaly priced (under Rp 250.000), have a general brand or easy to find brand, with a comfort style or daily used design, and with branded speciality store with price as a value driver. Suggestion from this study are that the confection industry can make clothes with prices under Rp 250.000 in product development to face competition. Where women’s clothing consumers like a reasonaly price when making a purchase decision